PENGARUH PERTUMBUHAN EKONOMI TERHADAP KESEMPATAN KERJA (KASUS PROVINSI BALI, 2001--2011) - Dayuh Rimbawan, Nyoman (PIRAMIDA, 2012)
Job opportunities are considered as one of important targets in each phase of development process. Job opportunities are highly related to economic growth. The relation is expected to be positive, meaning that the higher the economic growth the more job available. Therefore it is important to ensure the high rate of economic growth. However, economic growth and job opportunities are not always in line, even though the economic growth is high job opportunities grow slower. Consequently, many workforces stay unemployed and increase poverty level. During 2001 – 2011 the economy of Bali grew 5.57 percent per year in average, but job opportunities only grew 3.36 percent. Job opportunity elasticity and ILOR are the methods that can be used to describe the effect of economic growth on job opportunities creation. In the period of 2001 – 2011 the job opportunity elasticity of Bali was less than one. This means that the capability of economic growth to create job opportunities is low. ILOR rate for the period in average was less than 10.000 persons. Thus in Bali poor people are still found, about 2.3 percent per year; income distribution is also imbalanced which is shown by the increasing Gini Ratios. The low creations of job opportunities in Bali are due to: (1) Bali economic growth is mainly supported by consumption expenditures; (2) distribution of the use of GDP is dominated by consumption expenditures (71 percent) while investment reaches only 27 percent; and (3) in each year regional budget always earns a surplus (called SiLPA) which reflects unproductive funds.
Keywords: economic growth; job opportunities; unemployment and poverty